Fungal community characteristics and driving factors during the decaying process of Salix psammophila sand barriers in the desert. - Yumei Liang (Public Library of Science (PLoS), 2021)
Wood-inhabiting fungi are crucial to wood decay and decomposition in S. psammophila sand barriers, which in turn consumingly influence nutrient dynamics in desert soils. In the case of an extremely arid desert, as opposed to forests, little of known about the fungal community composition of decaying wood and the effects of decomposing wood on soil physical and chemical properties. Combined with high-throughput gene sequencing technology, we investigated the relationships between microenvironment factors with fungal community composition and diversity during the decomposition of Salix psammophila sand barriers. The results showed that the destruction of lignocellulose components during the decay process of S. psammophila sand barrier alters the physical and chemical properties of the surrounding soil. Compared with one-year sand barrier, lignin and cellulose of seven-year S. psammophila sand barrier decreased by 40.48% and 38.33%, respectively. Soil available potassium and available nitrogen increased by 39.80% and 99.46%, respectively. We confirmed that soil available nitrogen, soil pH and soil moisture content significantly affected the fungal community distribution of S. psammophila sand barriers. Sordariomycetes are mainly affected by the positive correlation of soil pH, while Eurotiomycetes are most affected by the positive correlation of soil moisture content and soil porosity. Although our results highlighted the importance of bidirectional interactions between fungi in decayed sand barriers and soil properties, their contribution to the desert ecosystem still needs further confirmation from future studies. However, overall our findings improved the current understanding of the sand barrier-soil interactions on the process of ecological restoration.